Multi‐Objective Evaluation Method for Efficient Water Energy Utilization in Multistage Hydraulic Turbines With Ultrahigh Water Head and Low Flow Rate - Zichao Zhang; Sanya Zhao; Yanpin Li (Energy Science & Engineering)
ABSTRACT In this article, a multi‐objective comprehensive evaluation method is established by comprehensively considering the power and shaft diameter of a multistage hydraulic turbine with an ultrahigh water head and low flow rate to utilize water energy efficiently. Using this method, several schemes for calculating the runner's geometric parameters are attained through the scheme design of different maximum numbers of stages and rotational speeds under different operating conditions of water pressure and flow rate. The reasonable schemes are determined by the maximum value in the intersection of runner diameter value ranges, the blade inlet angle β1 ≥ 12° and the blade inlet flow angle α1 ≥ 6°. Based on the multi‐objective function of water energy utilization considering the comprehensive performance of the runner diameter and power, the design parameters and design stage numbers of the multistage hydraulic turbine with the optimal comprehensive performance of power and shaft diameter are obtained. This method is recommended for the design of ultra‐low specific speed multistage hydraulic turbines with a specific speed of less than 50.